General Decay of the Moore–Gibson–Thompson Equation with Viscoelastic Memory of Type II - Salah Boulaaras; Abdelbaki Choucha; Andrea Scapellato (Journal of Function Spaces)
This study deals with the general decay of solutions of a new class of Moore–Gibson–Thompson equation with respect to the memory kernel of type II. By using the energy method in the Fourier space, we establish the main results.